2009
DOI: 10.1021/es902395h
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection of Airborne Asbestos Fibers Using Protein-Based Fluorescent Probes

Abstract: Fluorescence microscopy (FM) is one of the most important analytical tools in modern life sciences, sufficiently sensitive to allow observation of single molecules. Here we describe the first application of the FM technique for the detection of inorganic environmental pollutants-airborne asbestos fibers that can cause asbestosis, mesothelioma, and lung cancer. In order to assess FM capabilities for detecting and counting asbestos fibers, we screened E. coli lysate for proteins that bind to amphibole asbestos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…However, a recent study demonstrated that the DksA protein from Escherichia coli binds strongly and selectively to chrysotile, the most commonly used industrial form of asbestos, which now makes it possible to visualize the asbestos fibers in water by fluorescence microscopy. 4,32 In addition, the protein promotes stability of a chrysotile suspension by introducing steric repulsions between fibers. 33 …”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study demonstrated that the DksA protein from Escherichia coli binds strongly and selectively to chrysotile, the most commonly used industrial form of asbestos, which now makes it possible to visualize the asbestos fibers in water by fluorescence microscopy. 4,32 In addition, the protein promotes stability of a chrysotile suspension by introducing steric repulsions between fibers. 33 …”
Section: Introductionmentioning
confidence: 99%
“…This has led to proposals for new selective methods to detect asbestos in concrete materials [30,31].…”
Section: Ndmentioning
confidence: 99%
“…Recognizing the limitations of these methods, the National Institute for Occupational Safety and Health has recently identified development of improved analytical methods for asbestos fibers as a strategic research goal (National Institute of Occupational Safety and Health (NIOSH) 2011). An emerging alternative to the commonly used analytical methods is fluorescence microscopy (FM), which employs fluorescent staining by specific asbestos-binding probes to both visualize asbestos and distinguish it from the unstained non-asbestos fibers (Kuroda et al 2008;Ishida et al 2010Ishida et al , 2012Ishida et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to PCM, fluorescence microscopy provides a highly advanced capability to differentiate asbestos from non-asbestos fibers (Ishida et al 2010(Ishida et al , 2013. While this capability is below the level provided by electron microscopy, it does not require any advanced skills on the part of the operator.…”
Section: Introductionmentioning
confidence: 99%